Kształcenie na odległość uczniów i uczennic z lekką niepełnosprawnością intelektualną w czasie pandemii COVID-19 w opiniach nauczycieli i nauczycielek - Buchnat, Marzena; Jaskulska, Sylwia; Jankowiak, Barbara (Rocznik Pedagogiczny, 2021)
The text is a research report. The research aimed to diagnose and describe the distance education of students with mild intellectual disabilities during the COVID-19 pandemic from the perspective of teachers. The study consisted of answering questions contained in a survey disseminated by the In- ternet. 114 correctly completed surveys were collected. In the light of the results, teachers are more convinced that it is possible to implement the core curriculum during distance education than the educational, and especially caring function of the school. Teachers also expressed the opinion that distance learning exacerbates rather than equalizes differences between students, which is particu- larly worrying for students with mild intellectual disabilities.